Forecasting the Course of Cumulative Cost Curves for Different Construction Projects - Szóstak, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Planning the course of cumulative cost curves and effectively monitoring the implementation process and the incurred financial outlays are still significant problems in the management of construction projects. This is particularly noticeable during the execution phase of construction works. Therefore, it is worthwhile to correctly determine the shape of the cost curve before starting this stage and to periodically examine its fitting to the scheduled course of the budgeted cost curve, the envelope of cost curves characterised by the best-fit curve.
Keywords: construction project; cumulative cost; Three Sigma rule